Wahdatul Wujud dalam Perspektif Hamzah Al Fansuri dan Syeikh Siti Jennar - Anton Noverdin (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: Wahdatul Wujud in the Perspective of Hamzah Al Fansur and Sheikh Siti Jennar. One of the early figures who spread Sufism in the archipelago was Shaykh Siti Jenar, who was famous for his concept which was a controversy about the issue of life and death, God and freedom, and the place where the Shari'a was applied. Sheikh Siti Jenar views that human life in this world is called death. On the other hand, what is generally called death is the beginning of an essential and eternal life by him. As a consequence, human life in this world cannot be subject to worldly laws, such as state law. In this study, the author uses a library research method that focuses on aspects of thinking, the history of the two figures, as well as other figures who influence them. So in conducting library research, make a collection of primary and secondary books, which are related to all references that support this writing study. Hamzah Fansuri has thoughts about wahdatul embodiment or embodiment, namely: first, the essence of being, that there is only one being, namely Allah, even though the forms appear to be many. Both Eka in Diversity, that form does not only include its unity even though it has many forms. Third, the creation of nature, the process of creating nature starts from la ta'ayyun, ta'ayyun, tanazzul, by going through the five dignity (phases), and will bertaraqqi to la ta'ayyun while Shaykh Siti Jenar's thoughts about divinity are what are famous on the island of Java as Manunggaling Kawula lan Gusti, which in the author's understanding is almost the same as the teachings of the Wahdatul Being. Where God and nature are one entity or God is immanent with nature (humans). Keywords: Wahdatul Wujud, Perspective of Hamzah Al Fansuri, and Perspective of Sheikh Siti Jennar Abstrak: Wahdatul Wujud dalam Perspektif Hamzah Al Fansuridan Syeikh Siti Jennar. Salah satu dari tokoh awal yang menyebarkan ajaran tasawuf di kepulauan Nusantara ini adalah Syaikh Siti Jenar, yang terkenal dengan konsepnya yang kontroversial tentang persoalan hidup dan mati, Tuhan dan kebebasan, serta tempat berlakunya syariat tersebut. Syekh Siti Jenar memandang bahwa kehidupan manusia di dunia ini disebut sebagai kematian. Sebaliknya, apa yang disebut umum sebagai kematian, justru disebut sebagai awal dari kehidupan yang hakiki dan abadi olehnya. Sebagai konsekuensinya, kehidupan manusia di dunia ini tidak dapat dikenai hukum yang bersifat keduniawian, misalnya hukum negara. Dalam riset ini penulis menggunakan metode penelitian kepustakaan (Library Research) yang memfokuskam kepada aspek pemikiran, sejarah dari dua tokoh serta tokoh-tokoh lainya yang mempengaruhinya. Maka dalam mengadakan penelitian kepustakaan penyusun melakukan pengumpulan dari buku-buku primer maupun sekunder, yang ada kaitanya dengan seluruh referensi yang mendukung studi penulisan ini. Hamzah Fansuri memiliki pemikiran tentang wahdatul wujud atau wujudiyyah, yaitu: pertama Hakekat Wujud, bahwa wujud itu hanya satu yaitu Allah meskipun wujud itu kelihatan banyak. Kedua Eka dalam Keanekaan, bahwa wujud bukan hanya mencakup kesatuannya meskipun ia bertajalli dalam banyak bentuk. Ketiga Penciptaan Alam, proses penciptaan alam dimulai dari la ta’ayyun, ta’ayyun, tanazzul, dengan melalui lima martabat (fase), dan akan bertaraqqi kepada la ta’ayyun sedanngkan Pemikiran tentang ketuhanan yang dimiliki oleh Syaikh Siti Jenar adalah apa yang masyhur di pulau Jawa dengan sebutan Manunggaling Kawula lan Gusti, yang dalam pemahaman penulis hampir sama dengan ajaran dari paham wahdatul wujud. Dimana Tuhan dan alam adalah satu kesatuan atau Tuhan itu immanen dengan alam (manusia). Kata Kunci: Wahdatul Wujud, Perspektif dari Hamzah Al Fansuri, dan Perspektif dari Syeikh Siti Jennar